Estimating wider economic impacts in transport project prioritisation using ex-post analysis - Glen Weisbrod (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2016)
Transport project prioritisation and selection processes require consideration of many aspects of costs, intended benefits and other impacts. Economic analysis methods can measure many of those factors, though the analysis methods must be specified in ways that meet the information needs of decision-makers. This paper examines how benefit-cost analysis, economic impact analysis and multi-criteria analysis approaches have evolved and been applied to address the specific form of governmental decision processes that exist in the U.S. and some other countries. It discusses how "ex-post" case studies and associated statistical studies of have been promoted and utilised to both inform and refine "ex-ante" evaluation methods. It concludes by discussing the advantages, limitations and trade-offs involved in the use of this approach for transport project decision-making.
Keywords: 330; Verkehrsinfrastruktur; Projektmanagement; Kosten-Nutzen-Analyse; Entscheidung; USA